2015
DOI: 10.1002/ajmg.b.32309
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 gene variants and antidepressant treatment outcome: A meta‐analysis

Abstract: The efflux pump P-glycoprotein (P-gp), a gene product of the ABCB1 gene, plays a pivotal role in the transfer of various molecules across the blood-brain barrier. P-gp protects the brain by selectively extruding its substrates, including certain antidepressive drugs, thereby limiting their uptake into the brain. Uhr et al. [2008] first showed that ABCB1 variants predicted the remission to antidepressants with P-gp substrate properties in patients suffering from major depression (MD). Other studies investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 45 publications
(106 reference statements)
3
32
2
1
Order By: Relevance
“…Additionally, we have previously found an influence of CYP2C19 and CYP2B6, but not of ABCB1 , on sertraline pharmacokinetics which was also confirmed in this study. However, other polymorphisms in ABCB1 , such as rs2032583, rs2235040 and rs9282564, but not C3435T , have earlier been linked with remission and side effects of depressive patients treated with sertraline . It is necessary to clarify whether this or other polymorphisms in ABCB1 can affect sertraline disposition and then have an impact on patients' outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have previously found an influence of CYP2C19 and CYP2B6, but not of ABCB1 , on sertraline pharmacokinetics which was also confirmed in this study. However, other polymorphisms in ABCB1 , such as rs2032583, rs2235040 and rs9282564, but not C3435T , have earlier been linked with remission and side effects of depressive patients treated with sertraline . It is necessary to clarify whether this or other polymorphisms in ABCB1 can affect sertraline disposition and then have an impact on patients' outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a significant association has been reported between a SNP in the gene encoding PGP, (ATP-binding cassette, sub-family B member 1), and MDD [220]. Meta-analysis of 16 pharmacogenetic studies on PGP polymorphisms identified the rs2032583 SNP that was nominally associated (P = 0.035) with anti-depressant treatment outcome [221]. MDD patients undergoing anti-depressant treatment had significantly increased PGP function as measured by positron emission tomography [222].…”
Section: Therapeutic Considerations In Mood Disordersmentioning
confidence: 99%
“…Multiple studies with conflicting results have been conducted since an association with treatment was reported in 2008 [25]. A recent meta-analysis of 16 pharmacogenetic studies concluded that two SNPs -rs2032583 and rs2235015 are significantly associated with antidepressant treatment outcome for inpatients with depression when treated with antidepressants that are substrates of P-glycoprotein [27]. The C allele of rs2032583 and the T allele of rs2235015 of the ABCB1 gene lead to better rates of remission [28].…”
Section: Abcb1 and Drug Transportmentioning
confidence: 99%